Application of Gellan Gum Biopolymer in Biomedical Applications: A Review - Hishamuddin, Norsyakirah Izzati; Razali, Mohd Hasmizam; Mat Amin, Khairul Anuar (UI Scholars Hub, 2022)
Gellan gum (GG) has gained considerable attention in the food, chemical, and pharmaceutical industries due to its functional characteristics. It has versatile properties, such as water solubility, easy bio-fabrication, good film/hydrogel-formation, biodegradability, and biocompatibility. These properties render GG a promising material in biomedical applications, specifically in the development of wound dressing materials. In this review, the use of GG biopolymer as a wound dressing material was discussed. Various fillers, such as titanium dioxides, clay, drug, and honey, have been incorporated in GG to produce film, hydrogel, or scaffold materials. The effects of filler on the mechanical performance, physical properties, antibacterial activities, and healing activities of GG biocomposites were explained. Overall, this review summarizes the effect of fillers on GG biocomposites for various biomedical uses.